EVALUASI KEBIJAKAN EMISI GAS BUANG DAN ALTERNATIF RAMAH LINGKUNGAN DARI PERSPEKTIF PENGGUNAAN KENDARAAN BERMOTOR DI DINAS LINGKUNGAN HIDUP KOTA BENGKULU - Dekki, Dekki; Dani, Rahiman; Aprianty, Henny (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The increase in the number of motor vehicles in Bengkulu City has a significant impact on air pollution due to exhaust gas emissions. This study aims to evaluate exhaust emission control policies and identify potential environmentally friendly vehicle alternatives. The research uses a qualitative descriptive approach with data collection techniques through interviews, observations, and documentation. The results show that even though the emission policy has been implemented, its implementation is still not optimal due to the lack of socialization, supervision, and supporting facilities. Motor vehicle emissions, especially from older vehicles, produce pollutants such as CO, NOx, and HC that exceed safe thresholds. Alternatives to green vehicles such as electric vehicles and biofuels have been introduced, but they face obstacles such as high prices and lack of infrastructure. This study recommends increasing regulatory enforcement, public education, and green infrastructure development to support emission reduction programs in Bengkulu City. Keywords: Exhaust emissions, environmental policy, environmentally friendly vehicles